Phytotoxin produced by Bipolaris euphorbiae in-vitro is effective against the weed Euphorbia heterophylla - Barbosa,Aneli M. (2002)
Four virulent strain isolates of the fungus, Bipolaris euphorbiae (previously identified as a Helminthosporium sp.), isolated from host plants in four states within Brazil were screened for the production of phytotoxins that promoted wilting and defoliation of the Brazilian weed, Euphorbia heterophylla, commonly found growing among soyabean crops. Only one isolate, B. euphorbiae Strain I (EUPH petropar from Mato Grosso state), produced phytotoxin in-vitro when grown in stationary culture for 7 d at 28 ° C on minimum salts medium supplemented with 1.5 % glucose as the sole carbon source. Phytotoxin was also produced when the fungal strain was grown on fructose, galactose, mannose, xylose and sucrose. The addition of nitrogen source (yeast extract, peptone or malt extract) to the culture medium did not influence phytotoxin production. The phytotoxin produced by Strain I was most active at pH 6.0, stable between pH 3-9, and was highly thermostable, remaining fully active when heated at 90 ° C for 1 h.